Proceedings of the 2nd International Media Conference 2019 (IMC 2019) 2020
DOI: 10.2991/assehr.k.200325.031
|View full text |Cite
|
Sign up to set email alerts
|

Factors of Public Self-Disclosure Via Instagram Stories

Abstract: Openness is an important factor in relationship maintenance. However, excessive self-disclosure can jeopardize the privacy or security of one's own identity. Therefore, we need to manage the boundaries between private or public information. This privacy management explained by Sandra Petronio in the Communication Privacy Management Theory (CPM). Before the rise of social media, someone usually conveys private information face to face to others who have personal closeness. Yet, social media changes the old mann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 2 publications
(6 reference statements)
2
0
0
Order By: Relevance
“…Its followers are screened based on their familiarity with the informants, and usually, only close friends (roughly 10% of the total first account follower number) made it into the list. This data is supported by previous research, which showed that Instagram users in Indonesia strongly consider privacy concerns (Purmiasa et al, 2020).…”
Section: We Have the Right To Be Friends With Anybody If All My Frien...supporting
confidence: 88%
See 1 more Smart Citation
“…Its followers are screened based on their familiarity with the informants, and usually, only close friends (roughly 10% of the total first account follower number) made it into the list. This data is supported by previous research, which showed that Instagram users in Indonesia strongly consider privacy concerns (Purmiasa et al, 2020).…”
Section: We Have the Right To Be Friends With Anybody If All My Frien...supporting
confidence: 88%
“…Being able to customise and restrict the information they share aligns with Gen Z's concerns for privacy (Seemiller & Grace, 2017). This fact is in line with surveys conducted among 400 respondents in Indonesia's five big cities, which found that Instagram users also consider "what information" and "to whom" the information is shared, as emphasised by Sandra Petronio in Communication Privacy Management Theory (Purmiasa et al, 2020).…”
Section: Introductionsupporting
confidence: 57%